Empowering Thai SMEs through IT competency, digitalization and digital transformation for new product development - Pittawat Ueasangkomsate (Cogent Business & Management)
Small and medium-sized enterprises (SMEs) in Thailand’s food industry face challenges in competitiveness due to limited resources, low technological adoption, and workforce constraints. While digitalization and IT competency are recognized as drivers of innovation, their interconnected roles in digital transformation and new product development (NPD), creating unique products or services, remain underexplored. This study examines the mediating role of digitalization between IT competency and digital transformation and explores how digital transformation influences NPD to enhance the competitiveness of Thai food SMEs. Grounded in dynamic capability theory, data were collected through an online questionnaire distributed to representatives of Thai food SMEs listed in the Ministry of Commerce’s warehouse database. Conducted between December 2021 and February 2022, the study obtained 83 valid responses from a sample of 2665 (3.1% response rate). Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis reveals that digitalization fully mediates the relationship between IT competency and digital transformation, which significantly enhances NPD. The findings highlight IT competency, digitalization, and digital transformation as key drivers for innovation, offering strategic insights for policymakers and practitioners. This study also advances dynamic capability theory and emphasizes the need for Thai SMEs to adopt technological capabilities to remain competitive in emerging markets.